Periodontal changes in patients undergoing radiotherapy - Marques, MAC; Dib, L. L. (Amer Acad Periodontology, 2004)
Background: the purpose of this study was to evaluate changes in the periodontium in patients who received head and neck radiation therapy.Methods: Periodontal clinical parameters (probing depth, clinical attachment level, gingival recession, plaque index, and bleeding on probing) were assessed on 27 patients before and 6 to 8 months following radiation therapy in the head and neck area.Results: the greatest changes occurred in clinical attachment level: overall, 70.3% of the patients showed a loss, with 92% evincing loss in the mandible. Attachment loss was directly related to the field of radiation and was greater when the jaws were actually included in the irradiated area.Conclusion: Periodontal status should be evaluated prior to and following radiation therapy in the oral-maxillary-facial region to help ensure that periodontal health is maintained in oncology patients.
Keywords: head and neck neoplasms/radiotherapy; periodontal diseases/etiology; periodontium; radiation effects